A sludge-modified foam concrete for road fill material: Performance evaluation and carbon footprint analysis - Weihao Li; Jiapeng Yang; Ming Sun; Fengxia Xu; Yan Zhao; Handuo Xia (Journal of CO2 Utilization)
Foam concrete, as a common road fill material, has long been widely studied. This paper examined the compressive strength, water absorption rate, freeze-thaw resistance, Young's modulus, erosion resistance, and thermal conductivity of foam concrete with various densities and sludge contents. SEM and XRD images were utilized to study the impact of different sludge levels on hydration products. Environmental impacts were analyzed using life cycle assessment, and the optimal mix ratios were determined using the TOPSIS method. Results showed that incorporating a small amount of sludge (10 %) does not significantly impact the performance of foam concrete and can even slightly enhance compressive strength at a density of 800 kg/m3. The addition of sludge altered the internal pore structure, reduced thermal conductivity, decreased freeze-thaw resistance and Young's modulus, but improved erosion resistance and promoted the formation of AFt and AFm. Foam concrete with a density of 800 kg/m3 and 10 % sludge content exhibited the best overall performance. Substituting sludge for cement in foam concrete production effectively reduces carbon emissions.